Perlindungan Hukum terhadap Konsumen dalam Transaksi Live Shopping pada Platform E-Commerce - Tonny Soetrisno; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The live shopping phenomenon on platforms like TikTok Shop, Shopee Live, and Lazada Live dominates Electronic Commerce (PMSE) in Indonesia, yet its real-time and persuasive transaction characteristics pose new legal risks for consumers, such as misleading information and non-conforming goods. This normative juridical research aims to analyze the legal regulations, forms of consumer protection, and the responsibilities of business actors and e-commerce platforms. The results indicate that the Consumer Protection Law functions as lex generalis, while the Government Regulation on PMSE acts as lex specialis underlying real-time electronic contracts. The liability of business actors is strict (strict liability) or based on unlawful acts (Article 1365 of the Civil Code), whereas platforms are responsible as electronic system providers. However, protective effectiveness is hindered by fast-paced transactions, low digital literacy, and ambiguous streamer status. This study recommends strengthening technical regulations for content archiving and synchronizing policies for a fair digital ecosystem.